The European Union as a Participant of International Capital Flows, with the Example of Foreign Direct Investments - Attempt of Evaluation - Czech , Katarzyna (Studia Oeconomica Posnaniensia, 2018)
Foreign direct investment (FDI) are one of the major forms of cooperation among the participants of the modern world economy. The European Union has traditionally played a very important role both as an exporter and importer of capital in the form of FDI and was a major player in the process of capital flows in the global economy. However, since the beginning of the twenty-first century there has been a decrease in the role of the EU compared to the global flows of capital movements in the form of FDI. It was caused by the internal situation of the EU, related to, among others, further enlargements of the EU and the threat of Brexit, as well as by the impact of external factors such as the global economic crisis of 2007+. Despite the emergence of new parties actively participating in the international flow of FDI, as well as the materialization of Brexit, the EU as a whole will remain one of the leaders of those flows. Many of the member countries will also remain an attractive area for capital investment for foreign investors, with those from other EU countries as well as from outside of it. At the same time the capital from EU countries will be a source of financing for new technologies and will support a variety of industries both in other EU countries, including in particular the so-called. new member states as well as beyond.